Nursing Care in Schizophrenia Clients With Focus Study Risk of Violent Behavior - Nufush Chalida Ziaulkhaq; Erna Erawati; Angga Sugiarto; Suyanta Suyanta (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
There are around 20 million people worldwide suffering from schizophrenia. In Indonesia there is an increase in the number of schizophrenic clients, which were originally 1.7 per 1000 to 7 per 1000 population of Indonesia where Central Java is in the fifth position of mental disorders. The symptoms of schizophrenia are divided into 2 categories, positive and negative. Positive symptoms that can appear in schizophrenic clients, one of which is the risk of experiencing behavioral disorders, namely violent behavior. Violent behavior can result in loss of individual control so that it has the potential to hurt oneself, attack others and damage the environment. The purpose of this study is to describe nursing care from assessment to evaluation of schizophrenic clients with a focus on the study of the risk of violent behavior through interventions to control spiritual anger with murrotal ayat kursi. This research includes field research using descriptive analytic methods through case exposure with the nursing process approach. Research subjects are schizophrenic clients with risk of violent behavior. In this study using the instrument aggression questionnaire to measure the level of client aggression. The results showed the provision of nursing care to schizophrenic clients with the risk of violent behavior through intervention to control spiritual anger with murrotal ayat kursi showed improvement in the condition of the client which has a significant influence on mental status decline and aggression scores.